Prevalence and risk factors of needle stick and sharp injury among tertiary hospital workers, Vientiane, Lao PDR. Issue 6 (20th November 2017) - Matsubara, Chieko; Sakisaka, Kayako; Sychareun, Vanphanom; Phensavanh, Alongkone; Ali, Moazzam
Abstract : Objectives: Health care workers (HCWs) face risks of needle stick and sharp injuries (NSIs). Most NSIs occur in developing countries, however, no epidemiological study on NSIs is publicly available in Lao PDR. The objective of this study is to identify the prevalence and risk factors of NSIs among HCWs in Lao PDR. Methods: This cross‐sectional study was designed to determine the prevalence and risk factors of NSIs among four tertiary hospitals in Vientiane, Lao People's Democratic Republic. Results: Six months before the survey, 11.4% (106/932) of hospital staff had experienced NSIs, while 42.1% did in their entire career. Key protective factors of NSIs among nurses included adequate availability of needles, syringes, and sharp equipment ( p = 0.042; odds ratio [OR], 0.47) and attendance to educational or refresher courses on safety regarding NSIs ( p = 0.038; OR, 0.50). As an on‐site practice, single‐handed recapping was prevalent (46.7%, 257/550) among participants. Conclusions: The result showed that high rates of NSIs persist among HCWs. The findings of this research call for comprehensive health and injection safety programs for HCWs involved in clinical practice.